Degradation of VDMOSFET by Heavy Ion Irradiations - C. Salame; F. Pelanchon; P. Mialhe (Active and Passive Electronic Components)
This article focuses on the effect of the heavy ions irradiations on the electrical characteristics of VDMOSFET (Vertical Diffusion Metal Oxide Semiconductor Field Effect Transistor) devices. A summary of the total dose effects and the single event effects is covered to evaluate the experimental observations. Device degradations due to the hot carriers junction avalanche are studied by a physical parameters extraction method, leading to an understanding of the degradation processes. Results show that a protective resistor load can reduce the degradation effect in the device.